CHARACTERIZATION OF THE EFFECT OF ACELLULAR CRYOPRESERVED BIOLOGICAL AGENTS ON THE LEVELS OF ANTI-INFLAMMATORY AND REGULATORY CYTOKINES IN EXPERIMENTAL AUTOIMMUNE ARTHRITIS - Hladkykh, Fedir; Liadova, Tetyana (Eastern Ukrainian Medical Journal, 2024)
Background. The pathogenesis of rheumatoid arthritis (RA) involves a complex cascade of cytokines that trigger the proliferation of synovial cells and cause damage to both cartilage and bone. In recent years, particular attention has been drawn to research focused on exploring the potential use of acellular cryopreserved biological agents (CBAs) for optimizing RA therapy. Objective. The paper aims to characterize the effect of CBAs – placental cryoextract (PCE), spleen cryoextract (SCE), and conditioned medium from mesenchymal stem cells (MSC-CM) on cytokine levels in an adjuvant arthritis (AA) model. Methods. Experimental studies were conducted on 42 male rats weighing 200–220 g. AA was modeled by administering complete Freund’s adjuvant. On day 28 of the experiment, mixed blood samples were collected. The levels of interleukins (IL-2, IL-4, IL-6, and IL-10) were determined by enzyme-linked immunosorbent assay (ELISA). Results. It was found that on day 28 of the experiment, during AA development, there was a statistically significant (p<0.001) increase in the levels of anti-inflammatory cytokines – IL-4 by 94.9% and IL-10 by 150.7%, as well as an increase in the levels of regulatory cytokines – IL-2 by 233.3% (p<0.001) and IL-6 by 167.7% (p<0.001) compared to the intact rats. The administration of the studied cryoextracts had a pronounced effect on the levels of anti-inflammatory cytokines in AA rats. Specifically, following PCE administration, IL-4 levels decreased (p=0.004) by 31.3%, and after SCE administration, IL-10 levels decreased (p=0.02) by 20.5% compared to untreated AA rats. The most pronounced effect on the levels of regulatory cytokines was observed with the use of MSC-CM in AA rats. IL-2 levels decreased (p=0.003) by 21.5% compared to untreated AA animals. Conclusions. It was established that the administration of CBAs influences the levels of anti-inflammatory and regulatory cytokines in AA rats, indicating their potential in the therapy of autoimmune diseases. The results showed a decrease in the levels of anti-inflammatory cytokines, particularly IL-4 and IL-10, as well as a reduction in the levels of the regulatory cytokine IL-2 after the administration of CBAs, suggesting their modulatory effect on the immune response.